2010
DOI: 10.1099/vir.0.019513-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential interaction between cassava mosaic geminiviruses and geminivirus satellites

Abstract: Geminiviruses are often associated with subviral agents called DNA satellites that require proteins encoded by the helper virus for their replication, movement and encapsidation. Hitherto, most of the single-stranded DNA satellites reported to be associated with members of the family Geminiviridae have been associated with monopartite begomoviruses. Cassava mosaic disease is known to be caused by viruses belonging to nine different begomovirus species in the African continent and the Indian subcontinent. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 60 publications
(43 reference statements)
1
49
0
Order By: Relevance
“…The interaction is specific and usually limits Rep transreplication to its own genomic components (22,27,28). However, the betasatellites are transreplicated by a diverse range of begomoviruses (8,9,14,17,22,23,(29)(30)(31)(32), thus suggesting a more relaxed interaction between betasatellites and their helper begomoviruses. For example, Ageratum yellow vein betasatellite (AYVB) and Cotton leaf curl Multan betasatellite (CLCuMB) are transreplicated by noncognate helper begomoviruses (14,17,22,30,31).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction is specific and usually limits Rep transreplication to its own genomic components (22,27,28). However, the betasatellites are transreplicated by a diverse range of begomoviruses (8,9,14,17,22,23,(29)(30)(31)(32), thus suggesting a more relaxed interaction between betasatellites and their helper begomoviruses. For example, Ageratum yellow vein betasatellite (AYVB) and Cotton leaf curl Multan betasatellite (CLCuMB) are transreplicated by noncognate helper begomoviruses (14,17,22,30,31).…”
mentioning
confidence: 99%
“…The ␤C1 protein suppresses silencing, upregulates viral DNA levels in plants, assists with virus movement, and modulates virus host range (16)(17)(18)(19)(20)(21)(22)(23). Betasatellites share only the nonanucleotide [TAA TATTAC] sequence with the helper begomovirus, which is believed to serve as the origin of replication (6,8,9).…”
mentioning
confidence: 99%
“…They share a network of protein interactions with geminiviruses and are dependent on them for transreplication, encapsidation, and vector transmission. The only sequence shared between ␤-satellites and geminiviruses lies in the short origin of replication (36,46,47). TTV subviral molecule (TTV) sequences are almost identical to parts of the parental genome, including the proposed origin of replication for TTVs.…”
Section: Discussionmentioning
confidence: 99%
“…Both mono-and bipartite geminiviruses associate with single-stranded DNA satellites to form disease-inducing complexes (16,36,46,47,52,55).…”
mentioning
confidence: 99%
“…As whiteflies become more adapted to local climates and environments, geminiviruses will become one of the major constraints on agricultural production worldwide. The vast distribution and abundance of begomovirus isolates and continuously newly reporting species as well as high genetic diversity within species suggested that begomoviruses have high mutation rate and they produce highly diverse population in very short time [108].…”
Section: Molecular Based Approachesmentioning
confidence: 99%